2014
DOI: 10.1007/s00192-013-2290-9
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in pelvic floor muscle strength and endurance in South African women

Abstract: This file was dowloaded from the institutional repository Brage NIH -brage.bibsys.no/nih van der Walt, I., Bø, K., Hanekom, S., Rienhardt, G. (2014 Abstract:Introduction: Limited knowledge exists about pelvic floor muscle (PFM) function in ethnic groups. The aim of this study was to compare PFM strength and endurance in a group of black, white and mixed-race women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Although the in vivo axial stretch of the vaginal wall was determined in this study, there is still limited information on the mechanical loads that the vagina experiences in the body and throughout a woman's lifespan. For the protocols established herein, we leveraged values of resting in vivo pressure reported by van der Walt et al in human patients [68]; however, future experimental data are needed to quantify patient-specific values over time, the changes induced by prolapse, and the relation to animal models. Information on the in vivo configuration will be useful in future work to calculate linearized material stiffness and in vivo geometry using a nonlinear constitutive relation [69].…”
Section: Discussionmentioning
confidence: 99%
“…Although the in vivo axial stretch of the vaginal wall was determined in this study, there is still limited information on the mechanical loads that the vagina experiences in the body and throughout a woman's lifespan. For the protocols established herein, we leveraged values of resting in vivo pressure reported by van der Walt et al in human patients [68]; however, future experimental data are needed to quantify patient-specific values over time, the changes induced by prolapse, and the relation to animal models. Information on the in vivo configuration will be useful in future work to calculate linearized material stiffness and in vivo geometry using a nonlinear constitutive relation [69].…”
Section: Discussionmentioning
confidence: 99%
“…First, our study had a larger sample size and covered a wider age range compared with previous studies, in which participants tended to be younger. Additionally, ethnic differences may also be a contributing factor, given that previous literature has indicated that ethnicity can impact PFM strength 23,24 . Lastly, differences in the vaginal manometry instruments used across studies may also introduce bias into the data and contribute to differences in findings.…”
Section: Discussionmentioning
confidence: 99%
“…At least one estrous cycle (at estrus) prior to experimentation a balloon catheter measured intravaginal pressures in 3–6 months of age female Fbln5 + / + (n = 6), Fbln5 +/− (n = 6), and Fbln5 −/− with grade 1 POP (n = 5) mice 18 , 41 , 42 . A custom polyvinyl chloride 3 mm-diameter balloon was attached to a 1.25 mm-diameter aluminum tube to construct the balloon catheter 18 .…”
Section: Methodsmentioning
confidence: 99%